ATTRIBUTION ERROR TO THE VICTIM IN DOMESTIC VIOLENCE: A CONTEMPLATION OF DOMESTIC VIOLENCE OBSERVER - Irwan, Geby Chyntia; Margaretha, Margaretha (Jurnal Psikologi, 2020)
This study aims to determine the attitudes toward the violence, conducted by a husband to wife, focus on victim-blaming. In this study, the effect of demographic factors on the violence and victim-blaming was also analyzed. The respondents of this study were 458 college students aged 18 to 32 years. Two measuring instruments were used, namely: IBWB (Inventory of Beliefs about Wife Beating) and DVBS (Domestic Violence Blame Scale). The data was analyzed using stepwise regression, and the result shows a relationship between attitudes about violence against wife and victim-blaming (r=-.41, p<.001). Independent t-test of ANOVA shows the higher level of bias of gender role on the male as female. ANOVA and independent t test show that men have a higher level of gender role bias, but there is no significant difference in marital status or religion in blaming the victim. Stepwise regression analysis showed R2 = .03 for the gender variable, and R2 = .20. The R2 = .20 is a contribution from two variables, namely husband’s violent attitude to wife and gender. This can lead to the victim blaming in a domestic violence case. The implications of the findings are also discussed.